"Applauz winszowny JMCI Panu Stanisławowi" jako wzór zachowania językowego wspólnoty szlacheckiej = "Applauz winszowny JMCI Panu Stanisławowi" as a?pattern of language behavior of noble community - Szagun, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article concerns the seventeenth century occasional piece entitled "Applauz winszowny przy dorocznej festywie patrona świętego JMCI Panu Stanisławowi NN. konferowany". Applause belongs to panegyric poetry and represents the epigram genre of a clear praising character, created to celebrate the patronal feast of Stanislaus. In terms of the content, the text is an expression of recognition character, and above all an expression of the linguistic behavior of the noble community and as such bears the hallmarks of preservation linguistic behaviors pattern of that community.
Keywords: poezja okolicznościowa; panegiryczny; wzór zachowania językowego; wspólnota szlachecka; barok; occasional poetry; panegyric; pattern of linguistic behavior; noble community; baroque